2005
DOI: 10.1007/s10658-005-8675-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Juglone on Active Oxygen Species and Antioxidant Enzymes in Susceptible and Partially Resistant Banana Cultivars to Black Leaf Streak Disease

Abstract: The black leaf streak disease (BLSD), caused by Mycosphaerella fijiensis, is the most destructive disease of bananas and plantains around the world. Breeding for resistance is the most promising strategy to fight this disease especially in small farmer plantations. Mycosphaerella fijiensis produces many phytotoxins such as juglone, which can be used, jointly with field and inoculations under controlled conditions, for screening banana cultivars for BLSD-resistance. This non-host specific phytotoxin has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 50 publications
3
28
0
4
Order By: Relevance
“…Grande Naine treated with the hydrophilic phytotoxin F5b indicated that oxidative damage is involved in its mechanism of action. This finding agrees with reports on the role of ROS in the mechanism of action of juglone (Daub 1986;Daub and Ehrenshaft 2000;Heiser et al 1998;Remotti et al 1997), including its role in initiating the oxidation of ascorbic acid (Busogoro et al 2004b) and inducing ROS in banana varieties partially resistant (Fougamou) and susceptible (Grande Naine) to black sigatoka (El Hadrami et al 2005). Additionally, cercosporin, the phytotoxin produced by many Cercospora spp., when activated by light in the presence of oxygen, elicits the production of singlet oxygen and superoxide (Daub and Hangarter 1983;, and the enhanced ROS production that Sclerotinia sclerotiorum and Botrytis cinerea each induce in their hosts is correlated with increased virulence of the phytopathogen (Deighton et al 1999;Levine 2000, 2002;Tiedemann 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Grande Naine treated with the hydrophilic phytotoxin F5b indicated that oxidative damage is involved in its mechanism of action. This finding agrees with reports on the role of ROS in the mechanism of action of juglone (Daub 1986;Daub and Ehrenshaft 2000;Heiser et al 1998;Remotti et al 1997), including its role in initiating the oxidation of ascorbic acid (Busogoro et al 2004b) and inducing ROS in banana varieties partially resistant (Fougamou) and susceptible (Grande Naine) to black sigatoka (El Hadrami et al 2005). Additionally, cercosporin, the phytotoxin produced by many Cercospora spp., when activated by light in the presence of oxygen, elicits the production of singlet oxygen and superoxide (Daub and Hangarter 1983;, and the enhanced ROS production that Sclerotinia sclerotiorum and Botrytis cinerea each induce in their hosts is correlated with increased virulence of the phytopathogen (Deighton et al 1999;Levine 2000, 2002;Tiedemann 1997).…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism of action of the different lipophilic phytotoxins produced by M. fijiensis has been studied very little; however, it has been reported that their activity is light-dependent, they affect the chloroplast, and disturb the proton electrochemical gradient across the plasma membrane, increase electrolyte leakage, and induce an oxidative burst in Musa spp. (Busogoro et al 2004a, b;El Hadrami et al 2005;Harelimana et al 1997;Lepoivre et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…A similar kind of CAT-dependent resistance mechanism was reported in a M. fijiensis resistant banana cultivar (Beltran-Garcia et al, 2009). An early stimulation of ROS scavengers had been associated with pathogen resistance in Musa by assisting host cells to recover from the stress condition caused by ROS release against mycotoxins like juglone (5-hydroxy-1,4-naphthoquinone), a pathogenicity factor secreted by M. fijiensis (Hadrami et al, 2005). Thus, it appears that M. eumusae is attacked by ROS and the recovery of plant cells from ROS damaging effects includes balancing of intracellular redox potential and oxygen detoxification.…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…), es la enfermedad foliar más destructiva en musáceas, está considerada entre las ocho enfermedades que amenazan la seguridad alimentaria mundial y la del banano como principal especie fruticola tropical (Panissi, 2010;Álvarez et al, 2013;Drenth y Guest, 2016). El patógeno destruye el área foliar por efecto de la excreción de la fitotoxina "juglone", interrumpiendo el trasporte de electrones en las membranas del cloroplasto, provocando necrosis del tejido foliar (El Handrami et al, 2005;Amari et al, 2011). Además, se ha demostrado la activación de genes por parte del hongo durante el proceso patogénico con musáceas Noar y Daub, 2016a;Noar y Daub, 2016b).…”
Section: Introductionunclassified
“…Otra metodología de evaluación temprana, quizás la más usada, es la inoculación de M. fijiensis en vitroplantas a nivel de invernadero, donde se descartan los genotipos susceptibles (Abadie et al, 2008;Cuéllar et al, 2010). Por otra parte, desde que se descubrió que juglone es la principal toxina que produce M. fijiensis durante su proceso patogénico, se utiliza como fuente de inóculo para seleccionar tempranamente genotipos resistentes a la enfermedad (Giménez y Colmenares, 2004;El Handrami et al, 2005;Amari et al, 2011). En este contexto, el objetivo del presente estudio fue identificar el grado de tolerancia y/o resistencia de varios genotipos de musáceas presentes en Ecuador al ataque de Sigatoka negra, mediante metodologías de evaluación temprana.…”
Section: Introductionunclassified